3. How comprehensive can we be in the economic assessment of vaccines?. Issue 1 (1st January 2017) - Standaert, Baudouin; Rappuoli, Rino
ABSTRACT: In two previous papers we argued on current vaccines economic assessment not fully comprehensive when using the incremental cost-utility analysis normally applied for treatments. Many differences exist between vaccines and drug treatments making vaccines economic evaluation more cumbersome. Four challenges overwhelmingly present in vaccines assessment are less important for treatments: requirements for population, societal perspectives, budget impact evaluation, and time focused objectives (control or elimination). Based on this, economic analysis of vaccines may need to be presented to many different stakeholders with various evaluation preferences, in addition to the current stakeholders involved for drugs treatment assessment. Then, we may need a tool making the inventory of the different vaccines health economic assessment programmes more comprehensive. The cauliflower value toolbox has been developed with that aim, and its use is illustrated here with rotavirus vaccine. Given the broader perspectives for vaccine assessment, it provides better value and cost evaluations. Cost-benefit analysis may be the preferred economic assessment method when considering substitution from treatment to active medical prevention. Other economic evaluation methods can be selected (i.e. optimisation modelling, return on investment) when project prioritisation is the main focus considered and when stakeholders would like to influence the development of the healthcare programme.